Applications in multicriteria decision making, data envelopment analysis, and finance - Lawrence, Kenneth D.; Kleinman, Gary (Applications of management science ;, 2010)
"Applications of Management Science" is a blind refereed serial publication published on an annual basis. The objective of this research annual is to present state-of-the-art studies in the application of management science to the solution of significant managerial decision-making problems. It significantly aids the dissemination of actual applications of management science in both the public and the private sectors. Volume 14 is directed toward the application of management science to multi-criteria decision making, Data Envelopment Analysis (DEA) and financial performance analyses. This volume is arranged in three sections. The first section focuses on multi-criteria decision making; the second focus is on the application of DEA to public schools, paper mills, nursing home quality, retailing, health care services, and performance efficiencies in cities. The third section focuses on multi-dimensional performance of a national stock market and the effect of organizational structure on micro-financial institutions. This volume will prove to be most valuable to those interested in financial performance measurements, productivity measurement and analysis, and management science, both as practitioners and researchers.